PENGALAMAN KARYAWAN GENERASI Z DALAM MENGIMPLEMENTASIKAN KEBIJKAN KERJA FLEKSIBEL: STUDI FENOMENOLOGI DI INDUSTRI KREATIF - Hesti Fauzianti; Fakhruddin Kurnia M (Paser Institute Management and Busines, 2025)
The purpose of this study is to analyze the employment practices of Generation Z in Indonesia’s creative industry. This phenomenon is particularly prominent in the context of significant post-pandemic transformation and the dominance of Generation Z in this sector. This study uses a phenomenological qualitative approach, conducting in-depth interviews and observations of six Generation Z employees working at a creative company in a metropolitan environment. The findings reveal that flexible work schedules are viewed positively as they support healthy work-life balance, enhance productivity, and strengthen employee trust and loyalty. However, significant challenges were also identified, including difficulties in managing work and personal life, unclear professional boundaries, limited face-to-face interaction, and adaptation to digital technology and virtual collaboration. This study highlights the importance of integrating psychological and social dimensions to develop adaptive, sustainable, and relevant career paths for Generation Z. The aim is to enhance well-being and productivity in the rapidly evolving creative industry.